Differences in eating patterns of middle school students living in urban and rural areas located in the Masovian Voivodeship - Marzena Malara; Natalia Zaleska; Grażyna Lutosławska (National Institute of Public Health - National Institute of Hygiene, 2018)
ABSTRACT Background. Proper eating behaviours among youth condition their bodies' optimal growth and development and impact future diet choices, which affects maintenance of health in later years. Studies concerning assessment of the way of eating among adolescents in Poland over the past years indicate a number of errors. Objective. The aim of these studies was to asses diet diversity of middle school students, living in urban and rural areas located in the Masovian Voivodeship. Material and methods. 180 people participated in this study, 90 girls and 90 boys in age between 13 and 15 years. They were middle school students, living in urban and rural areas of Mazowieckie Voivodeship. Assessment of the variety of eating pattern amongst participants were conducted using the Food Intake Diversification Questionnaire (FIVeQ). Results. It was found that 3.3% of respondents from rural areas and 10% of respondents from urban areas were characterized by inappropriate variation of food intake. Sufficient variation of food consumption was found among 35.5% respondents from rural areas and 36.6% from urban areas. Good variation of food consumption was demonstrated in 54.4% of subjects from rural areas and in 42.2% from urban areas. Very good variation of food consumption was found in 6,6% of subjects from rural areas and 11.1% from urban areas. It is worth noticing differences in diet variations observed in these studies. It was shown that diet variety at inadequate, good and very good level was significantly different between groups, which may be puzzling considering the fact that all subjects were living in the same Voivodeship. Conclusion. For reason being, results obtained in these studies indicate the need for education of young people on principles of balanced way of eating.